MODEL ECONOMIC ORDER QUANTITY (EOQ) DENGAN MEMENUHI BACKORDER DAN PERMINTAAN DENGAN PEMBAYARAN KREDIT 2 TINGKAT - Bella Guivera Diandes; Muhammad Subhan (UNIVERSITAS NEGERI PADANG, 2020)
Abstract— Generally, payment is made after the buyer receives the goods from the seller. At this time the development of the business world in Indonesia is increasingly rapid and various innovations have emerged, such as sellers will offer a delay in payments to buyers to complete transactions. This also applies to buyers to apply trade credit to their customers as a tool to attract customer interest to increase demand. Thus this paper will discuss the effect of a two-tier trade credit, on the optimal order quantity of an economical retailer with permitted shortages of goods. And assume the buyer demand function increases over time. The purpose of this inventory model is to maximize profits. With this, we model it in mathematical form. We can see the effect of the parameters on the decision variable of fulfilling the backorder and two-level credit payments. Keywords—EOQ, Backorder, Two-level trade credit.